2021
DOI: 10.1002/jcsm.12706
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic meta‐analysis of disuse muscle atrophy vs. resistance exercise‐induced hypertrophy in young and older humans

Abstract: Background Skeletal muscle atrophy manifests across numerous diseases; however, the extent of similarities/differences in causal mechanisms between atrophying conditions in unclear. Ageing and disuse represent two of the most prevalent and costly atrophic conditions, with resistance exercise training (RET) being the most effective lifestyle countermeasure. We employed gene‐level and network‐level meta‐analyses to contrast transcriptomic signatures of disuse and RET, plus young and older RET to establish a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 112 publications
(149 reference statements)
3
27
0
Order By: Relevance
“…In addition to dynapenic-abdominal obesity-induced inflammation and insulin resistance, mitochondrial dysfunction is considered a key factor in the development of CKD. 46 , 47 It has been reported that mitochondrial dysfunction in the kidney, including impaired mitochondrial dynamics with increased mitochondrial fragmentation, 48 reduced efficiency of mitochondrial biogenesis with downregulation of peroxisome proliferator-activated receptor-gamma coactivator-1 alpha, 49 and excessive mitochondrial oxidative stress 50 are associated with the development and progression of various kidney diseases, ultimately leading to CKD. In a recent study by Andres-Hernando et al, 51 the authors demonstrated that obese mice with sarcopenia markedly accelerated the progression of CKD and that the decrease in renal function was associated with more severe mitochondrial dysfunction, as indicated by mitochondrial numbers, expression of mitochondrial proteins, and intracellular levels of adenosine triphosphate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dynapenic-abdominal obesity-induced inflammation and insulin resistance, mitochondrial dysfunction is considered a key factor in the development of CKD. 46 , 47 It has been reported that mitochondrial dysfunction in the kidney, including impaired mitochondrial dynamics with increased mitochondrial fragmentation, 48 reduced efficiency of mitochondrial biogenesis with downregulation of peroxisome proliferator-activated receptor-gamma coactivator-1 alpha, 49 and excessive mitochondrial oxidative stress 50 are associated with the development and progression of various kidney diseases, ultimately leading to CKD. In a recent study by Andres-Hernando et al, 51 the authors demonstrated that obese mice with sarcopenia markedly accelerated the progression of CKD and that the decrease in renal function was associated with more severe mitochondrial dysfunction, as indicated by mitochondrial numbers, expression of mitochondrial proteins, and intracellular levels of adenosine triphosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Ten days of bed rest has been shown to induce ∼1-kg lean mass loss from the lower extremities and a 16% decline in knee extensor strength in older individuals ( 97 ), which was attributed to a 30% reduction in muscle protein synthesis ( 97 ). A metanalysis of transcriptomic data from studies of disuse or bed rest (≥7 days) revealed significant increases in transcripts involved in protein ubiquitination, immune signaling, and apoptosis and downregulation of genes involved in mitcohondrial organization and metabolic function ( 98 ), some of the pathways also seen in transcriptomics data from studies of frail elders ( 30 ). Other research also highlights bed rest-induced reductions in skeletal muscle protein synthesis that may underpin muscle atrophy and functional losses ( 99 , 100 ).…”
Section: The Physiological Phenotype Of Frailtymentioning
confidence: 99%
“…There are also several pathways and factors that contribute to the pathoetiology of muscle wasting and diseases. Although voluntary and forced muscle inactivity do not necessarily mirror contractile engagement ( 673 ), some of these could play a role in exercise training adaptation. For example, the levels of myostatin, which rise in several pathological states ( 15 ), are reduced by exercise ( 674 ), and the absence of myostatin signaling may be an important contributor to training adaptation.…”
Section: Acute Molecular Mechanisms Underpinning Endurance- and Resis...mentioning
confidence: 99%